DAMPAK GAYA KEPEMIMPINAN BERORIENTASI PRESTASI DAN IKLIM ORGANISASI TERHADAP KOMITMEN AFEKTIF DAAITV MELALUI KEPUASAN KERJA - Dina, Dina; Ginting, Ginta; Ariyani, Ida (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to ascertain the impact of independent factors like achievement-oriented leadership style and organizational climate. Affective commitment is a dependent variable, whereas job satisfaction is an intervening variable. The primary source of data for this quantitative study was an instantaneous Likert scale questionnaire delivered to each research participant. Employees of PT. X Jakarta and Medan make up the research population. A sample of 136 participants was selected using non-probability sampling techniques in conjunction with the purposive sampling approach. This study makes use of multivariate data analysis methods with the statistical model SEM-PLS. The results of the analysis show that there is a positive and significant effect of achievement-oriented leadership style on job satisfaction, affective commitment and affective commitment through job satisfaction. There is also a positive and significant effect of organizational climate on job satisfaction, affective commitment and affective commitment through job satisfaction. And there is a positive and significant effect of job satisfaction on affective commitment. These results provide managerial implications regarding how to increase employee affective commitment by paying attention to the achievement-oriented leadership style of the leaders and the organizational climate formed and increasing employee job satisfaction.